Impact of COVID-19 on Male Infertility: A Systematic Review - Guimarães Schmitz, Ana beatriz; Meyer Hastreiter, Bianca; Fucio Barros, Sarah Beatriz; TOLEDO SCOPARO BARIONI, CARINA; Boia Ferreira, Boia Ferreira (Brazilian Journal of Implantology and Health Sciences, 2024)
Since the beginning of the pandemic in December 2019, COVID-19 has reached significant dimensions. In this context, where all aspects of human life have been impacted, it is essential to understand the effects on male fertility, as studies suggest potential impacts on birth rates and the emotional well-being of thousands of couples. The objective of this study was to investigate the effects of the COVID-19 pandemic and its relationship with male infertility through a systematic review. Out of 99 results obtained from the search, 19 articles were selected for the review based on inclusion and exclusion criteria. Changes in seminal parameters, such as reduced concentration, motility, volume, and pH, were described and associated with various mechanisms, with inflammation and oxidative stress being the most prominent. This review concludes that there is a relationship between COVID-19 and male infertility, observable through semen analysis; however, as suggested and evidenced by all authors who assessed the post-infection period, after 2 months or more, fertility parameters are restored. Among authors who analyzed the issue of immunization, no relationship between vaccination and male infertility was reported, suggesting that the vaccine is safe. However, further studies are needed to determine whether immunization indeed interferes with male infertility.